Kajian Pemberdayaan Berbasis Partisipatif Wanita Pedagang Di Pasar Karangploso Kabupaten Malang - Warter Agustim; Retno Ayu Dewi Novita (BIP's JURNAL BISNIS PERSPEKTIF, 2014)
Gender issues are included in this category, generally women have a more diverse perception of the definition of poverty than men. Women's perceptions of poverty is not only related to access to income, assets, quality of education and health, food and opportunities, but also covers all aspects of life. In this study used qualitative methods in which there is no hypothesis testing, some of the elements used to describe the facts and circumstances that occurred in Women Traders Wholesale Markets in Karangploso Traditional Market, in this study, data was collected using questionnaires, interviews and observation. The use of purposive sampling method in this study aims to obtain information accurately and accordancely with the objectives of this study in which each sampling adjusted to predetermined criteria. The conclusion is the woman trader in Traditional Market of Karangploso need protection and guidance from various sides both cultures, leadership and entrepreneurship in which the presence of local cultural elements that limit the participation in the economy improve living standards.It could be concluded that the need for a companion program for perpetrators Women traders in the market environment Karangploso Kab. Malang both by the government, the private sector or the relevant parties.